VALENSI VERBA BAHASA MELAYU DIALEK PULAU PADANG KABUPATEN KEPULAUAN MERANTI - Mohd. Fauzi; Hermansyah Hermansyah; Juswandi Juswandi; T M Sum (Jurnal Ilmu Budaya, 2022)
This study aimed to explain the valence of Malay verbs in the Akit dialect of Padang island, Regency of Kepulauan Meranti. The method used was qualitative descriptive. The data was collected using the equivalent method and the observation method. The data used were oral and collected using interviews, observation, and intuition methods. The data analysis was used to split, deletion, substitution, and expansion techniques. The results of the data analysis were explained using the informal method. The results showed that Malay people on this island used the Malay language daily. Accordingly, the valence of the verbs found in the conversations of the Malay people on the island of Padang was one valence of verbs, two valences of verbs, and three valences of verbs. Through the passivation process, the three kinds of valence of the verbs could be derived from two valences of verbs became one and from three valences of verbs became two. One-valence verbs were bound by only one argument. Verbs with two valences were bound by two arguments at once, while verbs with three valences were bound by three arguments, while the process of decreasing valence could be done by passivation.